Policy context, coherence and disjuncture in the implementation of the Ideal Clinic Realisation and Maintenance programme in the Gauteng and Mpumalanga provinces of South Africa - Immaculate Sabelile Muthathi; Laetitia C. Rispel (BMC, 2020)
Abstract Background Universal health coverage is a key target of the Sustainable Development Goals and quality of care is fundamental to its attainment. In South Africa, the National Health Insurance (NHI) system is a major health financing reform towards universal health coverage. The Ideal Clinic Realisation and Maintenance (ICRM) programme aims to improve the quality of care at primary healthcare level in preparation for NHI system implementation. This study draws on Bressers' Contextual Interaction Theory to explore the wider, structural and specific policy context of the ICRM programme and the influence of this context on policy actors' motivation, cognition and perceived power. Methods This was a nested qualitative study, conducted in two NHI pilot districts in the Gauteng and Mpumalanga Provinces of South Africa. Following informed consent, we conducted in-depth interviews with key informants involved in the conceptualisation and implementation of the ICRM programme. The questions focused on ICRM policy context, rationale and philosophy, intergovernmental relationships, perceptions of roles and responsibilities in implementation, ICRM programme resourcing, and implementation progress, challenges and constraints. We used thematic analysis, informed by Bressers' theory, to analyse the data. Results A total of 36 interviews were conducted with key informants from national, provincial and local government. The wider context of the ICRM programme implementation was the drive to improve the quality of care at primary healthcare level in preparation for NHI. However, the context was characterised by contestations about the roles and responsibilities of the three government spheres and weak intergovernmental relationships. Notwithstanding examples of strong local leadership, the disjuncture between two national quality of care initiatives and resource constraints influenced policy actors' experiences and perceptions of the ICRM programme. They expressed frustrations about the lack of or diffuse accountability and their lack of involvement in decision-making, thus questioning the sustainability of the ICRM programme. Conclusions National health sector reforms should consider the context of policy implementation and potential impact on actors' motivation, cognition and power. All relevant policy actors should be involved in policy design and implementation. A clear communication strategy and ongoing monitoring and evaluation are prerequisites for implementation success.